2010
DOI: 10.1016/j.chemphyslip.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function relationships of the antigenicity of mycolic acids in tuberculosis patients

Abstract: Cell wall mycolic acids (MA) from Mycobacterium tuberculosis (M.tb) are CD1b presented antigens that can be used to detect antibodies as surrogate markers of active TB, even in HIV coinfected patients. The use of the complex mixtures of natural MA is complicated by an apparent antibody cross-reactivity with cholesterol. Here firstly we report three recombinant monoclonal scFv antibody fragments in the chicken germ-line antibody repertoire, which demonstrate the possibilities for cross-reactivity: the first rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…Although mycolic acids are ideal conservative compounds for Mtb confirmation studies, some territory, culturing, time of growth or physiological state related differences in their compositions were observed. Experimental data demonstrated that mycolic acids from Mtb, consisting mainly of alpha-, keto-, and methoxy-mycolates, contain mixtures of homologs with different chain lengths or stereochemistries around the functional groups in the main chain (Beukes et al 2010). These variables can possibly cause slight differences in the content of the single mycolic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Although mycolic acids are ideal conservative compounds for Mtb confirmation studies, some territory, culturing, time of growth or physiological state related differences in their compositions were observed. Experimental data demonstrated that mycolic acids from Mtb, consisting mainly of alpha-, keto-, and methoxy-mycolates, contain mixtures of homologs with different chain lengths or stereochemistries around the functional groups in the main chain (Beukes et al 2010). These variables can possibly cause slight differences in the content of the single mycolic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Antigenicity was also found to depend critically on the structure of the mycolic motif. In particular, methyl esterification of the carboxylic acid in the motif destroyed antigenicity altogether [126], possibly indicating a critical role of the carboxylic acid in stabilizing an antigenic conformational fold of the MA by hydrogen bonding with the oxygenated distal functional group.…”
Section: The Human Antibody Response To Mycolic Acidsmentioning
confidence: 99%
“…8 is that none of the MA isomers examined showed any significant difference in distinguishing between sera from TB-positive and TB-negative patients. The same applied to isomers of the keto-and alpha-MA classes [126].…”
Section: The Human Antibody Response To Mycolic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanospray voltage was Ϫ 1.35kV (negative ionization) All four antibodies were subsequently tested against a panel of synthetic and purifi ed lipids. Earlier studies had indicated that mycolic acid might have a similar 3D structure to cholesterol and evidence of cross-reactivity to cholesterol was observed in anti-mycolic acid antibodies previously isolated from a chicken phage display library ( 22,23 ). We therefore tested all four antibodies against purifi ed cholesterol and oxidized cholesterol derivatives.…”
Section: Mass Spectrometric Profi Ling and Quantifi Cation Of Mycolicmentioning
confidence: 99%